How Does AI Improve Quality Control in Medical Imaging? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2017)
In the realm of modern medicine, medical imaging stands as a cornerstone of diagnosis, treatment planning, and disease monitoring. The quality of medical ima...
Keywords: AI in Medical Imaging and Diagnostics; Improve; Quality; Control; Artificial Intelligence; Deep Learning; Healthcare